Vibrio tubiashii in France : description of pathogenic isolates affecting molluscs and study of their virulence mechanisms - Mersni-Achour, Rachida (CCSD, 2014)
The oyster farming constitutes one of the major components of the global aquaculture. However, this sector is facing abnormal mortalities outbreaks that affect diploid and triploid oyster at their different life stages, in the hatcheries and in the field. During bivalve molluscs mortality events in France, bacteria initially classified into Harveyi group, were regularly isolated along with herpes virus, V. splendidus or V. aestuarianus. In order to fine tune the taxonomic affiliation of those isolates, a genotypic and phenotypic approach was used. The bacterial isolates, initially misclassified into the Harveyi clade, were shown to be genetically closed to V. tubiashii strains already recognized as the main causative agents of larvae and juvenile mollusc mortalities in America and in England. A diagnostic tool was developed to evaluate its spread in mortality events since 2007, supporting this first description of V. tubiashii in France. Moreover, the virulence of isolates and the toxicity of their extracellular products (ECPs) were confirmed on C. gigas larvae and juveniles by experimental infections. Using in vitro assays, French V. tubiashii ECPs revealed their ability to alter some hemocytes immune defense probably through the degradation of matrix structural proteins. Finally, proteomic and transcriptomic analyses revealed the conjunction of multiples virulence factors including metalloproteases in the virulence of the French V. tubiashii strains. L’ostréiculture constitue l'une des principales composantes de l’aquaculture. Cependant, ce secteur est confronté à des épisodes de mortalités anormales survenant aussi bien en écloseries que dans le milieu naturel, affectant les huîtres diploïdes et triploïdes et à différents stades de leur vie. Pendant les épisodes de mortalité des mollusques bivalves en France, des bactéries, initialement classées dans le groupe de V. harveyi, ont été régulièrement isolées à coté des virus de type herpès, V. splendidus ou de V. aestuarianus. Afin d'affiner l’affiliation ...